Potential Combination of Red Onion and Bean Sprouts Extract as Natural Regulatory Substance (PGR) through Total Phenolic Analysis and Antioxidant Activity - Aristya, Cintania Putri; Anggarani, Mirwa Adiprahara (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Organic farming is now increasingly gaining attention as a solution to the challenges of environmental damage and the need for healthy food in the modern era. One important aspect of organic farming practices is the use of natural Plant Growth Regulators (PGRs) to increase crop yields and quality. This study aims to examine the potential combination of red onion and bean sprout extracts as natural PGRs through total phenolic analysis and antioxidant activity as a reference basis for further application to potato plants. Extracts from both materials were obtained through the maceration method, then formulated in six different ratio comparisons and analyzed for their total phenolic content using the Folin–Ciocalteu method and their antioxidant activity through the DPPH test. The results showed that variation B (8 g/L red onion + 2 g/L bean sprouts) had the highest total phenolic content of 14.77 mg GAE/g and the strongest antioxidant activity with an IC50 value of 173.7 ppm. The results were supported by the DMRT test, which showed significant differences between the combination variations. The content of natural hormones such as auxin, gibberellin, and cytokinin in both materials works synergistically in stimulating the biosynthesis of secondary metabolites such as phenolics, which contribute to antioxidant activity and its effectiveness as a PGR. Thus, variation B has the highest potential to be developed as an environmentally friendly and sustainable natural PGR to support the growth and resistance of potato plants. This formulation shows promising potential for further development in the field of organic farming and nature-based agricultural innovation.